(untitled) (OverHolland, 2017)
In November 2013 the Faculty of Architecture of Delft University of Technology hosted the exhibition Dogma: 11 projects + 1, which presented the first decade of research projects produced by the Rotterdam and now Brussels based architectural office led by Pier Vittorio Aureli and Martino Tattara. The exhibition was originally held in the beginning of 2013 at the Architectural Association in London and accompanied by the publication of a catalogue that included texts by the authors, an introduction by Brett Steel and a critical essay by the Italian scholar Gabriele Mastrigli.